An Innovation Of The Tahfidz Curriculum Model At Zhilalul Qur’an Boarding School In Jepara - Mu’alimatul Chasanah; Khalimatus Sadiyah (Insitut Muslim Cendekia, 2025)
This study investigated the renewal of Qur’anic learning design at Zhilalul Qur’an Islamic Boarding School in Jepara as part of a strategic transformation in curriculum system to align with contemporary educational demands. The research aimed to thoroughly examine the implementation of the tahfidz program within the boarding school-based learning environment, while also exploring key strategic innovations in its curriculum structure. The study focused to a single faith-based educational institution, Zhilalul Qur’an, to allow for an in-depth contextual analysis. Employing a qualitative interpretive approach, the study emphasizes in-depth exploration of social realities that cannot be quantified, with primary data obtained directly from informants involved in and possess comprehensive insights into the institutional dynamics and management of the boarding school. The findings revealed a substantial transformation in the tahfidz curriculum at Zhilalul Qur'an, marked to shift away from a monotonous independent memorization method. Instead, it implemented a classified learning system as part of renewed and more structured strategy in Qur'anic education.